VOLUME ESTIMATIONS FOR COMBINED FREE-WEIGHT AND RUBBER-BAND RESISTANCE EXERCISE (Kinesiology, 2017)
Volume, or the total work performed during resistance training is one of the vital variables of resistance exercise programming. The most common definition in use by practitioners is sets x reps x external weight. While appropriate for linear loading incurred through free-weight resistance exercise, this inadequately addresses the nonlinear loading incurred with rubber resistance, a relatively new loading technique. The purpose of this investigation was to derive a theoretical model to describe a method of volume calculation for rubber band plus free-weight exercise. Men (n=51; age 19.5±1.6 years; body height 1.76±0.07 meters; body weight 77.3±11.3 kilograms) and women participants (n=66; age 18.9±1.1 years; body height 1.65±0.07 meters; body weight 62.8±9.1 kilograms) were measured for band lengths incurred at: squat with knee extended position, squat with flexed position, and change in band length was then calculated. Significant gender differences were seen for band length change as a percentage of body height (p